1999
DOI: 10.1007/s002280050689
|View full text |Cite
|
Sign up to set email alerts
|

Drug extrapyramidal side effects. CYP2D6 genotypes and phenotypes

Abstract: CYP2D6-impaired metabolic capacity may be a contributory factor in extrapyramidal drug side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…This result is in agreement with those of our previous studies (Derenne et al, 1989;Perault et al, 1991;Vandel et al, 1999). It was probably due to the saturation of the metabolic pathways by the antidepressants.…”
Section: Phenotyping Datasupporting
confidence: 95%
See 1 more Smart Citation
“…This result is in agreement with those of our previous studies (Derenne et al, 1989;Perault et al, 1991;Vandel et al, 1999). It was probably due to the saturation of the metabolic pathways by the antidepressants.…”
Section: Phenotyping Datasupporting
confidence: 95%
“…Its genetic polymorphism is responsible for inter-individual differences in the therapeutic effect and toxicity of many drugs (Brosen and Gram, 1989;Chen et al, 1996;Spina et al, 1992;Spina et al, 1994;Vandel et al, 1999). Moreover with the same genetic basis, intra-individual CYP2D6 metabolic capacity variations are observed in patients, with possible clinical implications.…”
Section: Introductionmentioning
confidence: 97%
“…49 induced seizures was reported in relation to CYP2D6 activity 145 and several studies showed a relationship between extrapyramidal side effects of antipsychotic drugs and CYP2D6 polymorphisms. 96,[146][147][148][149][150][151][152][153][154][155][156] However, compared to the large efforts made to evaluate pharmacokinetic differences due to CYP polymorphisms, few prospective studies on benefit of phenotyping or genotyping for therapeutic outcome have been conducted so far. It was estimated from retrospective assessments that patients with psychiatric disorders Table 2.…”
Section: Impact Of Cyp2c9mentioning
confidence: 99%
“…The consequences of polymorphic enzymes on drug metabolism in relation to efficacy and side effects has been the focus of numerous studies (Vandel et al, 1999;Dandara et al, 2001). For instance, individuals lacking the expression of a polymorphic drug-metabolizing enzyme (commonly referred to as "poor metabolizers" or PMs) will have higher drug exposure if those drugs are metabolized by those polymorphic enzymes, which could lead to exaggerated pharmacology or enhanced side effects relative to the intermediate metabolizer and extensive metabolizer (EM) subjects given the same dose (Mahgoub et al, 1977).…”
Section: Introductionmentioning
confidence: 99%